CORPORATE SOCIAL RESPONSIBILITY DAN TURNOVER INTENTION: MEDIATOR KOMITMEN AFEKTIF DAN WORK MEANINGFULNESS - Regita, Indah; Wulandari, Fitri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025, 2025)
This study examines the impact of Corporate Social Responsibility (CSR) on employee Turnover Intention in a palm oil plantation company, considering the mediating roles of Affective Commitment and Work Meaningfulness. Using a quantitative method with purposive sampling, data were collected through questionnaire distribution to 139 respondents and analyzed using PLS-SEM. The results show that CSR has a positive effect on Affective Commitment and Work Meaningfulness, and a negative effect on Turnover Intention. Furthermore, Affective Commitment and Work Meaningfulness are proven to be partial mediators in the relationship between CSR and Turnover Intention. These findings highlight the importance of CSR as a corporate strategy to enhance employee retention. Strengthening CSR programs can create a more supportive work environment, increase employee satisfaction, and improve overall organizational stability. Thus, CSR contributes not only to social and environmental sustainability but also plays a vital role in maintaining a loyal and productive workforce. The implications of this study emphasize the significance of CSR in fostering a positive work environment and improving employee retention.